23 CO-DESIGNING A PRIMARY-CARE INTERVENTION TO REVERSE FRAILTY AND BUILD RESILIENCE THROUGH PUBLIC AND PATIENT INVOLVEMENT WITH OLDER PEOPLE. (25th October 2022) - Travers, J; Romero-Ortuno, R; Cooney, M-T; Shé, É Ní
Abstract: Background: An essential consideration in health research is to conduct research with members of the public rather than for them. Public and Patient Involvement (PPI) of older people in research can improve enrolment, relevance and impact. However, few studies with PPI in frailty research have been identified. PPI has fallen during the Covid-19 pandemic. We aimed to involve older people in co-designing a Randomised-Control Trial (RCT) intervention to reverse frailty and build resilience. We also wished to encourage wider use of PPI with older people by outlining our approach. Methods: Involvement of older people was undertaken in three stages. Eighteen over 65-year-olds helped co-design an exercise intervention in two group discussions using the Socratic education method. Ninety-four contributed intervention feedback in one-on-one telephone interviews over nine months. Ten contributors helped optimise the intervention in three online workshops. Multidisciplinary team input and systematic review supported co-design. Results: Eleven home-based resistance exercises were co-designed by group discussion contributors (mean age 75, 61% female). Frailty intervention format, gender balance and GP follow-up were shaped in telephone interviews (mean age 77, 63% female). Dietary guidance and patient communication were co-designed in workshops (mean age 71, 60% female). Technology proved no barrier to PPI. The co-designed frailty intervention is being evaluated in a definitive RCT. Conclusion: We enabled meaningful involvement of 112 older people in co-design of an intervention to reverse frailty and build resilience in diverse ways. Inclusive involvement can be achieved during a pandemic. Feedback enhanced intervention feasibility for real-world primary-care.